SIKAP DAN MOTIVASI PRAMUWISATA BALI BERBAHASA KOREA TERHADAP WISATAWAN KOREA SELATAN KE BALI - Yuniari, Putu Yolanda; Suwena, I Ketut; Sasrawan Mananda, I Gusti Putu Bagus (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Bali has an attractive spot for South Korean tourists who are traveling to see their beautiful sceneries. Based on visitor statistics report as a result, the number of South Korean tourists has decreased significantly, and make an impact to tour guides in Bali. Tour guide becomes one of important profession to promote Bali as a tourist destination. The objectives of this research are to recognize a Korean tour guide’s attitude towards South Korean tourists in Bali and the motivation that makes them survived in this industry. This research applies a qualitative descriptive analysis method with Likert scales. Its samples have chosen by purposive sampling with the amount of 100 tour guides in Bali. Data collection techniques are conducted using observation, questionnaires, interviews, literature studies, and documentation. The results of the research are divided into three indicators namely, cognitive, affective, conative and it shows from attitude variable, the indicator dominates with very agree statement is few of South Korea tourists who visit Bali with score 4.11. Meanwhile, in motivation variable are divided into two indicators namely pull and push factor. The results are tour guides becomes an activity to support their family is a pull factor and there is job opportunity become a tour guide is a push factor indicator.